Analysis of Factors of Utilizing Dental Patient Services During the Covid-19 Pandemic to Kertawinangun Health Center, Indramayu Regency - Suharja, Eliati Sri; Pugarwati, Sri; Robbihi, Hilmiy Ila (International Journal Of Drug Research And Dental Science, 2022)
Background: First Level Health Facilities (FKTP) during the Covid-19 pandemic are very much needed, especially in public health center services to prevent, detect and respond in the prevention and control of Covid-19. This is part of what must be done in order to control the number of cases more. The public health center must also be able to manage, utilize existing resources effectively and efficiently in breaking the chain of transmission, both at the individual, family, and community levels. The factors that influence the use of dental patient services during the covid-19 pandemic are very diverse Material and Methods: This research is an analytic observational with a cross-sectional design. The population in this study were all patients who used the dental and oral health services at the Kertawinangun Health Center, Indramayu Regency, with the sampling procedure carried out by purposive sampling, a sample of 34 patients. Data were collected through observation, questionnaires, and documentation. Data were analyzed by multivariate analysis in this study was conducted using path (pathway analysis) Results: There is a significant difference in the use of dental patient services during the Covid-19 pandemic to the Kertawinangun Public Health Center, Indramayu Regency based on predisposing factors (attitudes and perceptions), reinforcing factors (distance and time), and enabling factors (attitudes dental health workers and family support) with a probability value of 0.000 <0.05. Conclusion: The use of dental patient services is very supportive for treatment at the Kertawinangun Health Center even during the covid-19 pandemic.